Swimbladder properties of Cyclothone spp. in the northeast Atlantic Ocean and the Western Mediterranean Sea - Sarmiento-Lezcano, Airam N.; Olivar, M. Pilar; Caballero, María José; Couret, María; Hernández-León, Santiago; Castellón, Arturo; Peña, Marian (Frontiers in Marine Science, 2023)
Non-migratory bristlemouth fishes (Cyclothone spp.) are the most abundant vertebrates on Earth and play an important role in the biological carbon pump by remineralizing organic carbon in deep ecosystems. Acoustic data and net sampling are often used in combination to estimate fish and zooplankton biomass, but this procedure may be subject to several sources of error when applied to mesopelagic species. For instance, the allocation of echoes to species has often been biased by not considering Cyclothone spp. due to the use of nets targeting larger fish. Furthermore, the acoustic properties of the target organisms must be well understood to convert acoustic density into numerical density. The characteristics of a fish’s swimbladder are the most relevant features necessary to assess its acoustic properties. This study provides information on the swimbladder properties of six Cyclothone species inhabiting the meso- and bathypelagic layers in the North Atlantic Ocean and Mediterranean Sea, including swimbladder location within the body, fat tissue content, morphology, morphometry (only available for C. braueri and C. pseudopallida), and fish body-mass density (only available for C. braueri, C. pseudopallida, C. pallida, and C. pygmaea). The studied species showed a functional physoclistous swimbladder, with well-developed gas glands and rete mirabile and numerous capillaries in the case of the shallower species C. braueri and C. pseudopallida (mainly distributed from 400 to 600 m depth), and a fat-invested swimbladder in species with deeper vertical distribution (C. livida, C. microdon, C. pallida, and C. pygmaea). The fat content in the swimbladder (C. pallida and C. microdon) increased with depth and latitude, reducing the space in the swimbladder that could contain gas. Changes in swimbladder size and volume during growth were analyzed for shallower species, where swimbladder volume and equivalent radius followed negative allometric growth in relation to body length. Finally, values of body-mass density (ρ) and gas content required for neutral buoyancy (VG) were estimated for C. braueri and C. pygmaea collected between 350 and 550 m (ρ = 1.052–1.072 g·cm−3, VG = 2%–4%; ρ = 1.052–1.062 g·cm−3, VG = 3.6%), and for C. pallida and C. pseudopallida sampled in the 450–700 m layer (ρ = 1.052–1.062 g·cm−3, VG = 2.6–3.1%; ρ = 1.052–1.062 g·cm−3, VG = 2.8%–3.25%). Results in this study highlight the change in scattering behavior of Cyclothone species from gas-bearing organisms (those that contain gas in their swimbladder) in the upper mesopelagic zone to the fluid-like scattering (with fat-filled swimbladders) of the deeper and northern individuals. The data presented in this manuscript are important for parametrizing acoustic backscattering models built to estimate the echo of Cyclothone species, although further work is needed, particularly for individuals with partially invested swimbladders with an irregular fat-free shape.